Decomposition of and nutrient release from ruminant manure on acid sandy soils in the Sahelian zone of Niger, West Africa - Esse, P.C.; Buerkert, Andreas; Hiernaux, Pierre H.Y.; Assa, A. (Elsevier, 2001)
In agopastoral systems of the semi arid West African Sahel, targeted applications of ruminant manure to the cropland is a widespread practice to maintain soil productivity. However, studies exploring the decomposition and mineralisation processes of manure under farmers' conditions are scarce. The present research in south west Niger was undertaken to examine the role of micro organisms and meso fauna on in situ release rates of nitrogen (N), phosphorus (P) and potassium (K) from cattle and sheep goat manure collected from village corrals during the rainy season. The results show that (1) macro organisms played a dominant role in the initial phase of manure decomposition; (2) manure decomposition was faster on crusteb than on sandy soils; (3) throughout the study N and P release rates closely followed the dry matter decomposition; (4) during the first 6 weeks after application, the K concentration in the manure declined much faster than N or P At the applied dry matter rate of 18.8 Mg ha t , the quantities of N, P and K released from the manure during the rainy season were up to 10 fold larger than the annual nutrient uptake of pearl millet (Pennisetum glaucum L.), the dominant crop in the traditional agro pastoral systems. The results indicate considerable nutrient losses with the scarce but heavy rainfalls which could be alleviated by smaller rates of manure application. Those, however, would require a more labour intensive system of corralling or manure distribution.